(untitled) (Academic Journal of Internal Affairs, 2020)
According to the government decree no. 72/2020. (III. 28.) Korm. On Hospital Commander and Protection of Health Stock the minister responsible for law enforcement – Sándor Pintér, deputy prime minister and minister for interior - made for control of health stock purchased by budget sources a proposal on appointment of hospital commanders to health institutes. According to that higher leader of the Police control and coordinate the economization of health institutes using health stock purchased by budget sources. The leader of the health institute is obliged to fulfil the regulations of the hospital commander on containment of pandemic and on safekeeping of health stock. On the other side a hospital commander must not give proposals and take decisions in medical professional topics. About practical fulfilment and handling of eventual problems and further about the application of the „Hungarian invention” of transit network we asked Dr. Zsolt Halmosi, pol. major general, deputy director of the Hungarian Police Director for law enforcement, and newly appointed national commander-in-chief for hospitals. He was asked by Zsuzsanna Hornyik. After termination of the special legal order we will ask Dr. Zsolt Halmosi to summarize experiences in handling the pandemic.